La Flexibilidad en piernas y Fundamentos de Fútbol de la Categoría sub-8. - Espinoza Anchaluiza, Lenin Omar (2023)
Knowing how flexibility works in soccer is necessary for a player's development since this will allow him to know the main functions of his performance in the game. In the same way, to avoid injuries, we must know precisely the muscle to work and the exercise he needs with respective time. It should be noted that soccer is one of the most valued sports worldwide. The technical foundations of soccer at an early age are a fundamental element since it allows for illustrating the athlete's training process and mastering the player's individual and collective actions. However, above all, it is the attraction of the rural sectors of Ecuador, the leaders of each sector have implemented championships in each of these areas, but it is necessary to strengthen their capacities with technical training in such a way that the children of our country can be part of the significant national and international leagues. Within this investigation, we will learn about flexibility, physical abilities, and child motor development, which allows us to know more broadly the functioning of the human body in the field of play.